PENINGKATAN KETERAMPILAN BIDANG PEMASANGAN INSTALASI LISTRIK RUMAH TANGGA DAN BIDANG SERVICE PERALATAN ELEKTRONIK BAGI PEMUDA PANTI BUDI UTAMA DI LUBUK ALUNG - Oriza Candra; Elfizon Elfizon; Hendri Hendri; Aslimeri Aslimeri; Aswardi Aswardi (JTEV (Jurnal Teknik Elektro dan Vokasional), 2019)
Budi Utama Adolescent Child Care Social Institution located in the suburb of Alung, Padang Pariaman Regency, consists of several majors including the Department of Electricity, Electronics, Electricity Use, Automotive, and Welding. PSAABR accommodates children and adolescents from underprivileged and school dropouts, also accommodates assisted children who have tripped over legal issues since 2015 and come from all over West Sumatra. For children assisted by the law, skills training and coaching such as children and other adolescents are also added with more specialized mental coaching. The number of fostered children in the PSAABR reaches 150 children. With 70 foster children and 80 adolescents built. For foster children, fostered parents are given special skills that are grouped based on the existing department. Skill improvement training in the field of domestic electrical installation and electronic equipment service fields. Besides being very helpful to them, obtaining skills also helps in developing independence and entrepreneurship and will keep them away from uncertainty about the future. The results of community service activities will improve the skills and competencies of participants, namely (1) Increasing knowledge of work safety standards, (2) improving the domestic electricity field, and (3) Increasing skills in the field of electronic equipment.